1995
DOI: 10.1159/000236947
|View full text |Cite
|
Sign up to set email alerts
|

Importance of lnterleukin-4 and lnterleukin-12 in Allergen-Induced Airway Changes in Mice

Abstract: T helper 2 (Th2)-like cells are thought to play a crucial role in the pathogenesis of atopic asthma. In this study, we attempted to evaluate the in vivo effect of suppressing Th2 cell development on allergen-induced airway changes. Repeated exposure of actively sensitized C57B1/6 mice to aerosolized ovalbumin (OA) causes, in comparison to saline-exposed control animals, synthesis of specific IgE, increase of eosinophils in bronchoalveolar lavage fluid and airway hyperresponsiveness. These effects are not obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
44
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 6 publications
8
44
2
Order By: Relevance
“…Augmented levels of IL-4 in BALF (42) and increased expression of IL-4 mRNA in BAL cells (43,44) have been recognized in patients with allergic inflammation. In murine models, IL-4 has been reported to be important for the development of allergic airway inflammation (45)(46)(47) and AHR (48,49). In our study we observed a significant decrease in BALF IL-4 levels.…”
Section: Discussionsupporting
confidence: 69%
“…Augmented levels of IL-4 in BALF (42) and increased expression of IL-4 mRNA in BAL cells (43,44) have been recognized in patients with allergic inflammation. In murine models, IL-4 has been reported to be important for the development of allergic airway inflammation (45)(46)(47) and AHR (48,49). In our study we observed a significant decrease in BALF IL-4 levels.…”
Section: Discussionsupporting
confidence: 69%
“…Additional evidence for the role of T H 2 cytokines in allergic diseases comes from the study of mice with targeted gene deletions. For example, murine models of asthma show decreased tissue and bronchoalveolar lavage eosinophilia in both IL-4 -/-and IL-5 -/-mice, as well as decreased hyperresponsiveness to methacholine following allergen exposure (16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…This induces Th1 responses and reduces IL-4 and IgE production in vitro and in vivo. [6][7][8][9] Although KW3110 and other LAB are potent IL-12 inducers, the mechanism for this activity has not been identified.…”
mentioning
confidence: 99%